2016
DOI: 10.18632/oncotarget.13392
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an HSP90 modulated multi-step process for ERBB2 degradation in breast cancer cells

Abstract: The receptor tyrosine kinase ERBB2 interacts with HSP90 and is overexpressed in aggressive breast cancers. Therapeutic HSP90 inhibitors, i.e. Geldanamycin (GA), target ERBB2 to degradation. We have previously shown that HSP90 is responsible for the missorting of recycling ERBB2 to degradation compartments. In this study, we used biochemical, immunofluorescence and electron microscopy techniques to demonstrate that in SKBR3 human breast cancer cells, GA strongly induces polyubiquitination and internalization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Although the anti-cancer efficacy of GA has been tested in many in vivo and in vitro studies, it has not yet been approved for clinical uses due to its structural instability and hepatotoxicity. However, GA is still commonly used for in vitro studies concerning HSP90 inhibition [ 192 , 193 ]. Similarly, RD usage was limited due to its instability as well [ 194 ].…”
Section: Role Of Hsp90 Isoforms In Pathological Conditionsmentioning
confidence: 99%
“…Although the anti-cancer efficacy of GA has been tested in many in vivo and in vitro studies, it has not yet been approved for clinical uses due to its structural instability and hepatotoxicity. However, GA is still commonly used for in vitro studies concerning HSP90 inhibition [ 192 , 193 ]. Similarly, RD usage was limited due to its instability as well [ 194 ].…”
Section: Role Of Hsp90 Isoforms In Pathological Conditionsmentioning
confidence: 99%
“…Although it was able to induce potent in vitro and in vivo cytotoxic effects, due to its structural instability and hepatotoxicity, its phase I clinical trial was suspended and it failed to progress further [ 253 ]. Despite the lack of success in the clinic, GM still plays fundamental roles as a potent HSP90 inhibitor for in vitro studies, especially in ERBB2+ breast cancer cells [ 254 , 255 ]. Another important natural inhibitor of HSP90 is radicicol (RD) ( Figure 9 (AII)), which was derived from Monosporium bonorden , which showed strong in vitro antitumor properties via attacking the core ATP-binding pocket of HSP90, but was proven ineffective in vivo due to its structural instability [ 256 ].…”
Section: Hsps and Their Role As Molecular Chaperones In Aiding Malmentioning
confidence: 99%
“…The different members of this signaling complex, which include ezrin, NHERF1, PMCA2, HSP90, EGFR or HER3, and HER2, appear to be involved in a series of interdependent interactions that stabilize and amplify HER2 expression and signaling within specific plasma membrane domains. Experience with HSP90 inhibitors has already suggested that disrupting the membrane stabilization of HER2 has clinical utility (12,57). Therefore, targeting other members of this complex singly or in combination might also be efficacious for the treatment of HER2-positive cancers.…”
Section: Ezrin Stabilizes Membrane Her2mentioning
confidence: 99%